In situ hydrolysis to produce catalyst-modified oxide thin film photoelectrodes
Patent Information
- Application Number
- CN202311356725.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-19
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-10-19
AI Technical Summary
由于氧化物半导体具有组分可调、带隙可控等特点受到广泛关注,但其本身固有缺陷,如电荷输运差和表面电荷复合严重,限制了其在PEC-WS应用中进一步推广
[0016]1、本发明在氧化物薄膜上负载有机金属框架纳米层,再利用尿素辅助工艺在MOF表面水解原位形成了超薄的LDH纳米片构建了MOF/LDH异质结。由于金属有机框架(MOF)和LDH之间的结构匹配产生了大量活性位点和界面缺陷,为贵金属纳米颗粒的锚定提供特殊的限制位点。通过调控氧化物薄膜结晶度、MOF及LDH层厚度、贵金属含量等参数,探明具有最佳载流子输运的结构配置。本发明中氧化物薄膜与LDH具有化学组成可调控的特性,催化剂之间的多金属协同作用能够改变催化剂的电子结构,改善了水分解反应的有效反应路径。同时单分散贵金属活性位点可以实现促进载流子有效输运,提高光电转换效率。
Smart Images

Figure CN117418268B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of photoelectric conversion and relates to an in-situ hydrolysis-generated catalyst-modified oxide thin film photoelectrode, its preparation method, and its application. Background Technology
[0002] Photoelectrochemical water splitting (PEC-WS) can convert solar energy into hydrogen energy, enabling the collection and storage of abundant solar energy into hydrogen fuel. Semiconductor photoelectrode materials reported for PEC-WS include oxides, sulfides, nitrides, and III-V compounds. Oxide semiconductors have attracted widespread attention due to their tunable composition and controllable band gap, but their inherent defects, such as poor charge transport and severe surface charge recombination, limit their further application in PEC-WS. Current research mainly focuses on improving PEC-WS performance through strategies such as enhancing light absorption efficiency, carrier separation efficiency, and transfer efficiency. Numerous studies have shown that surface engineering can effectively promote carrier separation and transfer by reducing surface recombination. Commonly used surface engineering methods include constructing oxygen evolution catalysts (e.g., FeOOH, NiOOH, Co-Pi), surface passivation layers (e.g., Al2O3, TiO2), and heterojunctions (e.g., Si / α-Fe2O3, BiVO4 / TiO2).
[0003] In recent years, researchers have focused on developing high-efficiency, low-cost catalysts. Uniformly dispersing ultra-low concentrations of noble metals on catalyst materials is an effective strategy for improving photoelectric efficiency. To prepare highly stable and active monodisperse noble metal catalysts, the mainstream strategy is to create defects on the surface of existing materials, providing sites for noble metal capture. Multimetallic layered double hydroxides (LDHs) are a typical layered material. Due to their unique two-dimensional layered structure, tunable composition, high specific surface area, abundant active sites, and large-scale production capabilities, their ability to be embedded between photoelectric layers allows for easy structural control, promoting surface catalytic kinetics and interfacial charge transfer at the solid-liquid interface, thus improving PEC-WS efficiency.
[0004] In this invention, the MOF / LDH composite structure generated by in-situ hydrolysis has a surface catalytic effect, which accelerates water activation to generate highly oxidizing active sites, thereby enhancing the photogenerated carrier separation efficiency of oxide films and significantly improving photoelectric conversion efficiency and PEC-WS performance. Summary of the Invention
[0005] This invention utilizes a catalyst generated by in-situ hydrolysis to improve the transport path of photogenerated carriers during PEC-WS. It proposes to form ultrathin LDH nanosheets on the surface of MOF using a urea-assisted hydrolysis process on oxide films, thus constructing a MOF / LDH heterojunction catalyst. The unique heterojunction between MOF and LDH provides a large number of sites for anchoring noble metal nanoparticles, thereby improving the performance of oxide film photoelectrodes in PEC-WS.
[0006] The present invention discloses an in-situ hydrolysis-generated catalyst-modified oxide thin film photoelectrode, which utilizes MOF in-situ hydrolysis to generate MOF / LDH heterojunction catalyst, and has abundant defects at the interface to anchor noble metal nanoparticles and increase active sites. The photoelectrode consists of an FTO substrate, an oxide thin film, a MOF and an LDH layer from bottom to top, and noble metal nanoparticles are anchored at the defects of MOF and LDH.
[0007] Furthermore, in the above technical solution, the oxide thin film includes α-Fe2O3, TiO2, WO3, ZnO, or BiVO4. These oxide thin film semiconductors can all be used as photoelectrodes.
[0008] Furthermore, in the above technical solution, the MOF catalyst is a transition metal catalyst, such as Fe, Ni, Co, Cu, Mn, etc. The LDH catalyst includes NiFe-LDH, NiCo-LDH, FeCo-LDH, etc. The anchored noble metal includes one of Ir, Ru, and Rh.
[0009] Furthermore, in the above technical solution, the oxide thin film layer is obtained by hydrothermal method, atomic layer deposition method, or thermal decomposition method; the catalyst is obtained by adsorption method, electrodeposition method, solvothermal method, or hydrothermal method; and the photoelectrode is grown with FTO / ITO as a conductive substrate.
[0010] Furthermore, in the above technical solution, the thickness of the oxide thin film photoelectrode (excluding the FTO substrate) is 450-550 nm (ideally 500 nm). Since the oxide thin film layer is deposited on the transparent conductive FTO substrate, the oxide thin film layer has a planar structure. The thickness of 450-550 nm (ideally 500 nm) not only helps to ensure good optical absorption, but also maintains good conductivity.
[0011] Furthermore, in the above technical solution, the thickness of the MOF / LDH layer is approximately 700–800 nm from the FTO substrate upwards. The defects generated in the processed heterostructure can provide sites for the modification of monodisperse noble metal particles in MOF / LDH.
[0012] Furthermore, in the above technical solution, a photoelectrode structure modified with an LDH catalyst generated by in-situ hydrolysis of MOF is constructed, as follows: Figure 1As shown.
[0013] This invention also provides a method for preparing the aforementioned oxide thin-film photoelectrode, comprising the following steps: using FTO as a substrate, high-temperature annealing to obtain an oxide thin film, growing a MOF layer on its surface, and then constructing an LDH layer matching the MOF structure through hydrolysis treatment; generating abundant defects at the heterojunction, and using the defect sites to anchor noble metal nanoparticles to provide active sites, thereby obtaining a composite oxide thin-film photoelectrode. By continuously controlling the concentration and reaction time during the reaction, an oxide thin-film photoelectrode modified with a noble metal-anchored MOF / LDH heterojunction catalyst with the highest photoelectrochemical water splitting performance is obtained.
[0014] The present invention further provides an application, namely, the application of the oxide thin film photoelectrode modified with the above-mentioned MOF / LDH heterojunction in the photoelectrochemical splitting of water.
[0015] Technical effect
[0016] 1. This invention loads an organometallic framework (MOF) nanolayer onto an oxide film, and then uses a urea-assisted process to hydrolyze and form ultrathin LDH nanosheets on the MOF surface in situ, constructing an MOF / LDH heterojunction. The structural matching between the MOF and LDH generates numerous active sites and interfacial defects, providing unique confinement sites for the anchoring of noble metal nanoparticles. By controlling parameters such as the crystallinity of the oxide film, the thickness of the MOF and LDH layers, and the noble metal content, the optimal structural configuration for carrier transport is determined. In this invention, the oxide film and LDH exhibit tunable chemical composition, and the multi-metal synergistic effect between the catalysts can alter the electronic structure of the catalysts, improving the efficient reaction pathway of the water splitting reaction. Simultaneously, the monodisperse noble metal active sites can promote efficient carrier transport and improve photoelectric conversion efficiency.
[0017] 2. This invention utilizes solvent and hydrothermal methods to prepare MIL-101(Fe)-modified α-Fe₂O₃ photoelectrodes, and employs a urea-assisted hydrolysis process to construct an in-situ MOF / LDH heterostructure on the MOF surface, enabling it to anchor noble metals. This promotes a 1.23V... RHE The photocurrent density is from 1.02 mA / cm² 2 Increased to 3.12 mA / cm 2 Furthermore, the initial potential shifted by approximately 0.2 V towards the cathode compared to the pure Sn@α-Fe2O3 photoelectrode. Carrier transport dynamics analysis indicates that the formed defect interface structure provides dispersion sites for the noble metal, maximizing the carrier transferability of the LDH carrier, improving conductivity and electronic synergy, and promoting carrier separation and transfer. Attached Figure Description
[0018] Figure 1 : Physical image of α-Fe2O3 photoelectrode modified with MOF catalyst supported by transition metal oxide; where: 1 is FTO / Sn@α-Fe2O3, 2 is α-Fe2O3 / MIL-101(Fe), 3 is α-Fe2O3 / MIL-101(Fe) / FeNi-LDH, and 4 is α-Fe2O3 / MIL-101(Fe) / FeNi-LDH@Ru.
[0019] Figure 2 Top view of α-Fe2O3 / MIL-101(Fe) / FeNi-LDH@Ru photoelectrode scanning electron microscope (SEM);
[0020] Figure 3 Cross-sectional image of α-Fe2O3 / MIL-101(Fe) / FeNi-LDH@Ru using a scanning electron microscope (SEM).
[0021] Figure 4 Transmission electron microscope (TEM) image of α-Fe₂O₃ / MIL-101(Fe) / FeNi-LDH@Ru photoelectrode;
[0022] Figure 5 X-ray diffraction (XRD) spectra of FTO / Sn@α-Fe2O3, α-Fe2O3 / MIL-101(Fe), α-Fe2O3 / MIL-101(Fe) / FeNi-LDH and α-Fe2O3 / MIL-101(Fe) / FeNi-LDH@Ru photoelectrodes;
[0023] Figure 6 UV-Vis absorption spectra of FTO / Sn@α-Fe2O3, α-Fe2O3 / MIL-101(Fe), α-Fe2O3 / MIL-101(Fe) / FeNi-LDH, and α-Fe2O3 / MIL-101(Fe) / FeNi-LDH@Ru photoelectrodes;
[0024] Figure 7 Photocurrent variations of FTO / Sn@α-Fe2O3, α-Fe2O3 / MIL-101(Fe), α-Fe2O3 / MIL-101(Fe) / FeNi-LDH, and α-Fe2O3 / MIL-101(Fe) / FeNi-LDH@Ru photoelectrodes under different bias voltages; where: at 1.23V RHE At a given photocurrent density, the MOF / LDH heterostructure photoelectrode with Ru sites loaded on an oxide thin film achieved a photocurrent density of 3.12 mA / cm². 2 Compared to a simple FTO / Sn@α-Fe2O3 photoelectrode, it improves efficiency by 205%;
[0025] Figure 8 The photoelectrodes FTO / Sn@α-Fe₂O₃, α-Fe₂O₃ / MIL-101(Fe), α-Fe₂O₃ / MIL-101(Fe) / FeNi-LDH, and α-Fe₂O₃ / MIL-101(Fe) / FeNi-LDH@Ru were used at 1.2V. RHE The photoelectrochemical impedance spectroscopy (PET) shows that the MOF / LDH heterostructure photoelectrode with noble metal Ru sites loaded on the oxide film has the minimum transmission resistance.
[0026] Figure 9 Mott-Schottky curves of FTO / Sn@α-Fe2O3, α-Fe2O3 / MIL-101(Fe), α-Fe2O3 / MIL-101(Fe) / FeNi-LDH and α-Fe2O3 / MIL-101(Fe) / FeNi-LDH@Ru photoelectrodes;
[0027] Figure 10 Graphs showing the changes in photogenerated carrier absorption and separation efficiency of FTO / Sn@α-Fe2O3, α-Fe2O3 / MIL-101(Fe), α-Fe2O3 / MIL-101(Fe) / FeNi-LDH, and α-Fe2O3 / MIL-101(Fe) / FeNi-LDH@Ru photoelectrodes under different bias voltages; where: 1.23V RHE The separation efficiency of photogenerated carriers was improved by 98.3% for the MOF / LDH heterostructure photoelectrode with noble metal Ru sites loaded on the oxide film (32.22%) compared with the simple Sn@α-Fe2O3 photoelectrode (16.24%).
[0028] Figure 11 Graphs showing the variation of photogenerated carrier transfer efficiency of FTO / Sn@α-Fe2O3, α-Fe2O3 / MIL-101(Fe), α-Fe2O3 / MIL-101(Fe) / FeNi-LDH, and α-Fe2O3 / MIL-101(Fe) / FeNi-LDH@Ru photoelectrodes under different bias voltages; where: 1.23V RHE The photogenerated carrier transfer efficiency of the MOF / LDH heterostructure photoelectrode loaded with noble metal Ru sites on the oxide film (76.29%) was improved by 58.24% compared with the simple Sn@α-Fe2O3 photoelectrode (48.21%). Detailed Implementation
[0029] To more clearly illustrate this technical solution, the following description, in conjunction with the accompanying drawings and embodiments, will provide further details:
[0030] α-Fe₂O₃ films were prepared via a hydrothermal reaction. An FTO substrate was sequentially ultrasonically cleaned with acetone, anhydrous ethanol, and deionized water for 15 min each. A mixed solution of 1.22 g FeCl₃·6H₂O and 0.27 g urea was dissolved in 50 mL of deionized water and poured into a polytetrafluoroethylene (PTFE) reactor to submerge the FTO substrate. The hydrothermal reaction was carried out at 100 °C for 12 h. After cooling, an iron hydroxide (FeOOH) film was obtained. This film was then immersed in a 0.1 mol / L SnCl₄ ethanol solution for 10 min to prepare Sn-doped FeOOH. The prepared Sn@FeOOH film was annealed in air at 500 °C for 2 h and then at 680 °C for 15 min to obtain FTO / Sn@α-Fe₂O₃ with a nanopillar morphology.
[0031] Surface composite catalysts were prepared by solvothermal and hydrothermal methods. 0.332 g of terephthalic acid and 1.616 g of Fe(NO3)3·9H2O were dissolved in 15 mL of N,N-dimethylformamide (DMF), and the mixture was stirred for 1 hour. The mixed solution and FTO / Sn@α-Fe2O3 were added to a polytetrafluoroethylene-lined stainless steel autoclave, heated at 120 °C for 24 h, cooled to room temperature, and the resulting product was filtered out. The product was purified by washing with DMF and ethanol, respectively, and then vacuum dried for 24 h to obtain octahedral MIL-101(Fe) attached to FTO / Sn@α-Fe2O3 nanorods. Weigh 14.5 mg Ni(NO3)2·6H2O and 6 mg CO(NH2)2 and dissolve them in 80 mL of distilled water. Immerse α-Fe2O3 / MIL-101(Fe) nanorods in the mixed solution and place them in a polytetrafluoroethylene-lined stainless steel autoclave. Heat at 100 °C for 10 h, cool to room temperature, filter out the product, wash and purify it with deionized water and ethanol respectively, and dry it to obtain the α-Fe2O3 / MIL-101(Fe) / FeNi-LDH photoelectrode.
[0032] In a mixed solution of 14.5 mg Ni(NO3)2·6H2O and 6 mg CO(NH2)2 dissolved in 80 mL of distilled water, 3.5 mL of 0.50 g / L RuCl3 solution was added. α-Fe2O3 / MIL-101(Fe) / FeNi-LDH@Ru photoelectrode was then immersed in the mixed solution under the same conditions as above.
[0033] Figure 2 SEM images show that the surface of the α-Fe2O3 / MIL-101(Fe) / FeNi-LDH photoelectrode has a uniform nano-network structure. Figure 3The thickness of the α-Fe₂O₃ / MIL-101(Fe) / FeNi-LDH photoelectrode is shown to be ~500 nm, and it is evident that the MOF / LDH composite heterostructure provides a rich interface for surface catalytic reactions. For example... Figure 4 As shown, the TEM image reveals that the nanoparticles are approximately 50 nm in size and exhibit a microcrystalline state, with a clear boundary between the thin film and the heterostructure. Figure 5 As shown, the XRD pattern confirms that the phase of the prepared oxide thin film photoelectrode is α-Fe2O3, and that loading the organometallic framework MIL-101(Fe) and LDH on the surface has no effect on the phase of α-Fe2O3. Figure 6 UV-Vis absorption spectroscopy analysis showed that the cutoff absorption edge of the α-Fe2O3 photoanode was about 600 nm, and the cutoff absorption edge of each photoanode with the introduction of a co-catalyst increased.
[0034] Figure 7 The performance of the Sn@α-Fe2O3 photoelectrode in PEC-WS with a MOF / LDH heterostructure and anchored noble metal Ru is shown. Compared with the FTO / Sn@α-Fe2O3 photoelectrode, the α-Fe2O3 / MIL-101(Fe) / FeNi-LDH@Ru photoelectrode performs better at 1.23V. RHE The photocurrent density at that location increased by 205% (from 1.02 mA / cm²). 2 Up to 3.12 mA / cm 2 ), and turn on the potential (U) on It shifted 0.2V towards the cathode. (For example...) Figure 8 As shown, 1.2V RHE Photoelectrochemical impedance spectroscopy (PET) shows that the α-Fe₂O₃ / MIL-101(Fe) / FeNi-LDH@Ru photoelectrode has a minimum radius. The semicircle diameter in the Nyquist plot represents the interfacial charge transfer resistance; a smaller diameter indicates improved catalyst performance, suggesting that the designed MOF / LDH heterostructure can effectively disperse and anchor the noble metal Ru, thus improving charge transfer. Figure 9 The figure shows the Mott-Schottky curves of the photoanode, where the α-Fe₂O₃ / MIL-101(Fe) / FeNi-LDH@Ru photoanode exhibits the highest charge density (N₂). D This indicates that the composite structure effectively increases the active sites of the metal, further demonstrating its superior PEC-WS activity.
[0035] Figure 10 The JV curves were tested under the condition of adding hole scavenger H2O2, and the carrier separation efficiency (η) was calculated. sep ) and transfer efficiency (η) tran). Calculation of η using α-Fe₂O₃ / MIL-101(Fe) / FeNi-LDH@Ru photoelectrode abs ×η sep The value was 32.22%, significantly higher than that of the FTO / Sn@α-Fe2O photoelectrode (16.24%). This is because the introduction of H2O2 can be considered as η... tran Since it is 100%, we choose to calculate η. abs ×η sep It can directly reflect η sep Size. For example... Figure 11 As shown, the α-Fe2O3 / MIL-101(Fe) / FeNi-LDH@Ru photoelectrode also exhibits the maximum η. tran The efficiency of the MOF / LDH heterostructure (76.29%) is significantly higher than that of the FTO / Sn@α-Fe2O3 photoelectrode (48.21%), α-Fe2O3 / MIL-101(Fe) photoelectrode (58.6%), and α-Fe2O3 / MIL-101(Fe) / FeNi-LDH photoelectrode (71.09%). Therefore, the MOF / LDH heterostructure and the introduced dispersed Ru sites can effectively increase the separation and transfer efficiency of photogenerated carriers.
[0036] The above data fully demonstrate the feasibility of this approach: FTO / Sn@α-Fe2O3 photoanodes are prepared via a hydrothermal method, and then MOF / LDH heterostructures are loaded onto the photoelectrode surface using a solvothermal and hydrothermal method, anchoring the noble metal Ru to improve carrier separation efficiency. In this approach, the unique layered structure exhibits a larger specific surface area, providing more active sites for noble metal anchoring. This improves the conductivity of the oxide thin-film photoelectrode, reduces surface carrier recombination, and significantly enhances the carrier separation efficiency and photoelectrochemical water splitting performance of the oxide thin-film photoelectrode.
[0037] The above embodiments describe the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the present invention. Various changes and modifications can be made to the present invention without departing from its principles, and all such changes and modifications fall within the scope of protection of the present invention.
Claims
1. A method for preparing a catalyst-modified oxide thin-film photoelectrode by in-situ hydrolysis, characterized in that, Includes the following steps: The FTO substrate was ultrasonically cleaned sequentially with acetone, anhydrous ethanol, and deionized water for 15 min each. FeCl3·6H2O and urea were dissolved in deionized water to prepare a mixed solution, which was then poured into a polytetrafluoroethylene reactor to immerse the FTO substrate. The hydrothermal reaction was carried out at 100 °C for 12 h. After cooling, an iron hydroxide FeOOH film was obtained, which was then immersed in a 0.1 mol / L SnCl4 ethanol solution to prepare Sn-doped FeOOH. The prepared Sn@FeOOH film was annealed in air at 500 °C for 2 h and then at 680 °C for 15 min to obtain FTO / Sn@α-Fe2O3 nanopillars. Terephthalic acid and Fe(NO3)3·9H2O were dissolved in DMF and mixed and stirred for 1 hour. The mixed solution and FTO / Sn@α-Fe2O3 were added to a polytetrafluoroethylene-lined stainless steel autoclave and heated at 120 °C for 24 h. After cooling to room temperature, the product was filtered out, washed and purified with DMF and ethanol, and vacuum dried for 24 h to obtain octahedral MIL-101(Fe) nanorods attached to FTO / Sn@α-Fe2O3 nanorods. RuCl3 solution was added to a mixed solution of Ni(NO3)2·6H2O and CO(NH2)2 dissolved in distilled water. The nanorods were then immersed in the mixed solution and placed in a polytetrafluoroethylene-lined stainless steel autoclave. The mixture was heated at 100 °C for 10 h, cooled to room temperature, filtered out, and purified by washing with deionized water and ethanol, respectively. After drying, the α-Fe2O3 / MIL-101(Fe) / FeNi-LDH@Ru photoelectrode was prepared.
2. The application of the oxide thin film photoelectrode obtained by the preparation method described in claim 1 in photoelectrochemical water splitting.
